Students’ perceptions of online reading behaviour at an institution of higher learning in South Africa: A pilot project - De Jongh, M.; Milton, C. (South African Journal of Higher Education, 2021)
Technological advances and the internet have altered the way people engage with reading material. Students’ reading preferences are increasingly screen-based as most students prefer and are required to use online reading in higher education institutions. The research explored the perceived impact of online reading on students’ reading comprehension and academic performance. A non-experimental research design was utilised for this survey, typically including the quantitative domain and, to a lesser extent, the qualitative domain. Seventy-one students who were available and consented completed the survey and included 20 first year, 19 second year, 22 third year and ten fourth year students. The results from a pilot study conducted on first to final year students at a department from a Health Care Sciences University indicated mostly positive feedback regarding the perceived effect of online reading on reading comprehension and academic performance. Most students prefer online reading as it is easily accessible, visually interactive and provides unlimited access to information. The results showed correlations and contradictions to the findings presented in the literature. Conclusions, recommendations and implications are made based on the findings of the study. The findings indicate that students, especially first-year entering students, should be prepared for online reading and be made aware of online reading techniques to support them in attaining academic literacy. These reading techniques could improve the throughput rate and lower the dropout rate in higher institutions in South Africa.